“Humanizing Humans” in Inclusive Pesantren: The Role of Peer Support in Promoting Self-Efficacy and Independence - Azizah, Nurul; Yusrina, Jihan Avie; Nugraini, Erna Dwi; Zulfa, Laila Ngindana (Jurnal Ilmiah Peuradeun, 2025)
Students with special needs in inclusive education settings, including Islamic boarding schools (pesantren), often face significant challenges related to low self-efficacy and limited independence. These difficulties are frequently rooted in feelings of alienation, low self-confidence, social withdrawal, and experiences of bullying. Peer support plays a vital role in fostering both self-efficacy and independence among these students. This study investigates how peer support contributes to the development of these attributes in inclusive Islamic boarding schools. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis, and were analyzed thematically using Quirkos software. The findings indicate that emotional, instrumental, and informational support from peers—especially when accompanied by unconditional positive regard and emotional availability—significantly enhances students’ self-efficacy and independence. The integration of Islamic values and the cultural context of pesantren nurtures a peer environment rooted in the philosophy of “humanizing humans”, which promotes inclusivity and challenges hierarchical perceptions of disability. This study provides valuable insights for inclusive education practitioners aiming to foster supportive peer relationships and inclusive school cultures.